The application of genome-wide CRISPR-Cas9 screens to dissect the molecular mechanisms of toxins - Bei Wang; Jun-Zhu Chen; Xue-Qun Luo; Guo-Hui Wan; Yan-Lai Tang; Qiao-Ping Wang (Computational and Structural Biotechnology Journal, 2022)
Many toxins are life-threatening to both animals and humans. However, specific antidotes are not available for most of those toxins. The molecular mechanisms underlying the toxicology of well-known toxins are not yet fully characterized. Recently, the advance in CRISPR-Cas9 technologies has greatly accelerated the process of revealing the toxic mechanisms of some common toxins on hosts from a genome-wide perspective. The high-throughput CRISPR screen has made it feasible to untangle complicated interactions between a particular toxin and its corresponding targeting tissue(s). In this review, we present an overview of recent advances in molecular dissection of toxins’ cytotoxicity by using genome-wide CRISPR screens, summarize the components essential for toxin-specific CRISPR screens, and propose new strategies for future research.